"In Despair, Despair Not": Ways to God for a Secular Age. (June 2020) - Duns, Ryan
While theological reflection on the question of secularism has been illuminating, it has not always provided resources for those still seeking to encounter God. By responding to Karl Rahner's paradoxical counsel—"in despair, despair not"—this article engages William Desmond and René Girard to uncover two distinct, yet complementary, "Ways" capable of returning seekers to God. When undertaken as a theological meditation, these "Ways" can awaken us to the graced order, the "order of charity, " in which we live.